Sonatas & partitas BWV 1004-1006 [compact disc] - Bach, Johann Sebastian, 1685-1750 (Harmonia Mundi, 2010)
Isabelle Faust has gone back to the original manuscript sources to offer us her version of a masterpiece of the violin repertoire. In Bachs time, music for solo instruments was still little explored territory, and his sonatas, partitas and suites immediately established themselves as a benchmark, technically challenging and brimming with creativity.